The Origins of Language An Introduction to Evolutionary Linguistics - Dornbierer-Stuart, Joanna (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XIX, 188 p. 23 illus., 2 illus. in color.